Temporal trends in the incidence and case severity of COVID-19 cases among the Syrian refugees in Azraq camp in Jordan: A retrospective observational study. - Ahmad Waleed Zghool; Ahmad Alrawashdeh; Zaid I Alkhatib; Sara A Nasser; Natalya Kostandova; Shiromi M Perera; Jomana W Alsulaiman; Adi H Khassawneh; Abdel-Hameed W Al-Mistarehi; Amer Abu-Shanab; Khalid A Kheirallah (PLoS Neglected Tropical Diseases)
Background Azraq Syrian refugee camp, located in Jordan, is where the challenges of managing the COVID-19 epidemic meet the vulnerabilities of displaced people. This study aimed to investigate the epidemiological characteristics, incidence, risk factors, and outcomes of COVID-19 among Azraq camp residents. Methods COVID-19 data from Azraq camp were collected by International Medical Corps clinics and analyzed retrospectively from August 1, 2020, to August 31, 2022. Data included demographics, risk factors, testing history, contact tracing, and vaccination profiles. We estimated COVID-19 incidence and analyzed risk factors using Poisson and multilevel logistic regression. Results A total of 2,468 confirmed COVID-19 cases were identified, with a prevalence of 5.6 per 100 residents. The camp's monthly incidence rate was more than 50% lower than the national rate, with a 1.7% monthly decrease. Females had a higher incidence than males (6.4% vs. 4.9%, p < 0.001), while the elderly bore the greatest disease burden. Home-based isolation was the main strategy, except during the second wave. Vaccination coverage reached 31.6%, primarily with Pfizer (49.8%). Symptomatic cases made up 44.0% of confirmed cases, with 10.4% requiring hospitalization. Factors independently associated with hospitalization included age, comorbidity, and vaccination status. Conclusion The study highlights the need for robust surveillance, targeted healthcare interventions, equitable resource allocation, and vaccination campaigns to manage COVID-19 and future epidemics in refugee camps.